2017
DOI: 10.1590/2317-1545v39n1165423
|View full text |Cite
|
Sign up to set email alerts
|

Use of image analysis techniques to determine the embryo size of Senna multijuga (Rich.) seeds and its relation to germination and vigor

Abstract: Semi-automatic evaluations of morphological attributes that are associated to seed germination performance such as the embryo size, have been of great interest when considering the study of image analysis techniques. The objective of this research was to evaluate the accuracy of the Tomato Analyzer software to quantify the variations on the embryo development degree of Senna multijuga seeds (Rich.) and its relationship with germination and tetrazolium tests. Seeds from four lots with different ripeness stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
1
10
0
2
Order By: Relevance
“…The morphometric variables showed no difference between lots although they have been constantly associated with the germinative performance of forest seeds. Marchi and Gomes-Junior (2017) observed a relationship between the area of seeds of Senna multijuga and its physiological potential. However, the authors emphasize that several aspects must be considered, such as the internal cavity occupied by the embryo and endosperm, the presence of mechanical damage, and spots indicating tissue deterioration or seed malformations, which can influence germination.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The morphometric variables showed no difference between lots although they have been constantly associated with the germinative performance of forest seeds. Marchi and Gomes-Junior (2017) observed a relationship between the area of seeds of Senna multijuga and its physiological potential. However, the authors emphasize that several aspects must be considered, such as the internal cavity occupied by the embryo and endosperm, the presence of mechanical damage, and spots indicating tissue deterioration or seed malformations, which can influence germination.…”
Section: Resultsmentioning
confidence: 94%
“…The use of the X-ray technique was satisfactory to identify these characteristics in a non-destructive, precise, and fast way. Other works have also successfully used the technique for analyzing seeds of forest species such as Tabebuia heptaphylla (Amaral et al, 2011), Acca sellowiana (Silva et al, 2013), Terminalia argentea (Gomes et al, 2014), Platypodium elegans (Gomes et al, 2016), Senna multijuga (Marchi and Gomes-Junior, 2017), Moringa oleifera (Noronha et al, 2018), Leucaena leucocephala (Medeiros et al, 2018), Lecythis pisonis (Rosa et al, 2020), Arctostaphylos pungens, Juniperus deppeana (Rubalcava-Castillo et al, 2020), and Pinus sibirica (Arkhipov et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…According to Abud et al (2018), studying broccoli seeds, the area of the seeds may reflect their vigor, since larger areas coincide with larger reserves available for seed germination and seedling growth. Marchi and Gomes Junior (2017) demonstrated that, for Senna multijuga seeds, it was the embryo area that most clearly expressed differences in the physiological quality of the lots in relation to the pericarp area. Likewise, larger values for embryo area were observed in lots 1, 6, 7, 8 and 10, indicative of the higher physiological quality of the seeds from these lots.…”
Section: Resultsmentioning
confidence: 99%
“…In regard to seeds, the use of non-destructive analyses, such as the X-ray test, has been documented as eff ective for studies of internal morphology of seeds of diverse species, such as Moquiniastrum polymorphum (Faria et al, 2019), Moringa oleifera (Noronha et al, 2018), and Leucaena leucocephala (Medeiros et al, 2018), among others. This technique assists in identifi cation of full seeds, empty seeds, mechanical damage, and spots that indicate deterioration, characteristics that can aff ect seed physiological potential (Marchi and Gomes Junior, 2017), and, consequently, the quality of seed lots.…”
Section: Introductionmentioning
confidence: 99%